Understanding cultural taste : sensation, skill and sensibility - Wright, David (Palgrave Macmillan, 2015)
"Understanding Cultural Taste updates and critiques established theoretical and empirical accounts of cultural taste. It takes account of the role of cultural industries and cultural policies in shaping cultural tastes and of the contemporary technologies through which cultural goods are produced, circulated and consumed. It weaves together a story of taste as bound up with sensation, skill and sensibility. Taking a historical and theoretical perspective which complicates an understanding of taste as either a matter of personal preference or a simple weapon in social struggles, the book argues that taste remains a significant and complex concept in the sociology of culture, media and cultural studies, cultural policy studies and in their applied sub-disciplines. Such disciplines have come to appreciate and accept the relation between taste and individual and group identities but have been less attentive to other social and political dimensions of this important component of cultural life"--